Risk Factors of Feline Lower Urinary Tract Disease in Banten, Indonesia - Thearza Tavinia; Faisal Fikri; AgusPurnomo; Shekhar Chhetri; SalipudinTasilMaslamama; Muhammad ThohawiElziyad Purnama (The Indian Veterinary Journal, 2023)
This study aimed to investigate the risk factors for cats associated with FLUTD, including age, breed, gender, feed, drinking water, behavior, and environmental factors in Banten, Indonesia. A total of 28 cats were enrolled in the present study then evaluated the history, physical examination, and urinalysis associated with FLUTD. The questionnaire was evaluated with the owner, then analyzed using the Spearmans’ correlation test followed by logistic regression.In result, male cats, physical intensity, changes in behavior, stress, and low intake of drinking water were highly significant factors in the increased incidence of FLUTD. Moreover, being overweight and giving dry feed types were also reported as significant factors attributed to FLUTD.This study also revealed three types of crystals in urine such as struvite crystals, oxalate, and cystine crystals.In conclusion, risk factors can be crucial evidence in monitoring FLUTD cases in the future.